Salinity and total dissolved solids measurements for natural waters: An overview and a new salinity method based on specific conductance and water type - McCleskey, R. Blaine; Cravotta, Charles A.; Miller, Matthew P.; Tillman, Fred; Stackelberg, Paul; Knierim, Katherine J.; Wise, Daniel R. (Applied geochemistry, 2023)
The total concentration of dissolved constituents in water is routinely quantified by measurements of salinity or total dissolved solids (TDS). However, salinity and TDS are operationally defined by their analytical methods and are not equivalent for most waters. Furthermore, multiple methods are available to determine salinity and TDS, and these methods have inherent differences. TDS is defined as the mass of anhydrous residue remaining in a sample vessel after evaporation and subsequent oven drying at a defined temperature. Salinity is a measure of the mass of dissolved salts in a given mass of solution. In addition, there are approaches that quantify the total solute (TS) concentration, including gases. The purpose of this study is to develop a proxy method using specific conductance and major-ion water type to reliably predict salinity, TDS, and/or TS. Thus, we compared several methods to calculate salinity, TDS, and TS for 6391 surface water samples and conclude the following: TDS measurements are best suited for studies of anhydrous residue (e.g., evaporites); salinity determined by summing the speciated ion concentrations, termed S∑spec, is the most comprehensive method to represent the concentration of dissolved constituents in natural waters; and TS determinations are useful if dissolved CO2 and other gases are of interest. Thus, we utilized S∑spec to compare differences between the various salinity, TDS, and TS methods, and to develop a new proxy method to predict salinity based on specific conductance (SC) and major ion water type, termed SSC_WT. For the surface waters used in this study, the median difference between TDS and S∑Spec was between −19% and −24%, depending on the method. The median difference between SSC_WT and S∑Spec was −2.4% for the samples in this study. The SSC_WT approach is cost effective, rapid, and capable of providing reliable real-time salinity determinations at surface water sites where SC data are available and water type is known. •Specific conductance and water type are used as a proxy measurement for salinity.•Salinity determined using chemical analyses and speciation is the most accurate and used to develop proxy.•Total dissolved solids measurements are substantially lower than salinity for many natural surface waters.•Salinity proxy measurements are cost effective, rapid, and can be high frequency.